Pengaruh Kualitas Produk, Promosi dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan di Kopi Kenangan - Dania Juniati; Anastasia Dian Putri.S; Mohammad Ridwan (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
Currently, coffee is a type of global drink that is famous in the world. Coffee is a very well-known commodity throughout Indonesia. Coffee, which was once synonymous with men and adults, has recently seen young people, especially women, increasingly enjoy drinking coffee. As coffee consumption increases from year to year, the coffee shop business has also experienced a significant increase. Every coffee shop is certainly adept at managing its business by having various concepts to attract customer attention. The aim of this research is to increase customer satisfaction at Kopi Kenangan by focusing on the role of product quality, promotion and service quality. Using IBM Statistics Version 26. Purposive sampling was used to collect samples from 81 customers, and the results showed that product quality had a positive impact on customer satisfaction while promotion had a positive impact and service quality did not. Together, product quality and promotion have a real and significant impact on customer satisfaction. Therefore, the purpose of this research is to improve product quality and promotional efforts at Kopi Kenangan so that it can better meet consumer needs and increase customer satisfaction.